The Performant Human Resources as a Condition of the Competitive Management - VĂCĂRESCU HOBEANU, Loredana (Journal of Research in Educational Sciences; Vol 11 No 1 (2020): JRES Volume XI Issue 1(13), 2020, 2020)
Since the beginning of the world, the individual saw the work need in his progress and his society. This need has led to the professional performance, which generated satisfaction and contentment at the work. The training and the continuous development of this become or should become a priority for both the company and the employee from the desire to achieve the best performance. The success and the competitiveness of the organizations depend largely on the employees’ professional performance and the ways to improve of this must become an urgent concern and also permanent; the economy competitive conditions. The organizations and the company stimulate and reward the performance in work and therefore the employee tends as much to achieve a professional performance. The performance key is all employees’ responsible and conscious involvement in achieving the mission and objectives of the organization. Based on these considerations this paper studies the role that the human resources performances have in the successful development of any activity .